2014
DOI: 10.1111/bjop.12059
|View full text |Cite
|
Sign up to set email alerts
|

Using risk model judgements to better understand perceptions of synergistic risks

Abstract: Numerous scientific studies show that risk factors can interact to synergistically increase the likelihood of certain adverse and life‐threatening outcomes. Yet, the extent to which individuals know that specific risk factor combinations present ‘synergistic risks’ is unclear and little is known about the determinants of such knowledge. This is largely because epistemological progress concerning this topic has been frustrated by a reliance on metrics that have latterly been judged to be of questionable validit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…Moreover, a study by Dawson et al . () indicated that awareness of certain synergistic health risks (e.g., lung cancer from exposure to radon and tobacco) may be a function of intuitively constructed mental models that depict the human body becoming much more vulnerable to harm when exposed to combinations of hazardous substances. Hence, an a priori causal theory of synergistic health benefits could be underpinned by the formation of rudimentary mental models that depict the human body becoming much more resilient to harmful substances and processes when bolstered by the presence of multiple beneficial factors.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, a study by Dawson et al . () indicated that awareness of certain synergistic health risks (e.g., lung cancer from exposure to radon and tobacco) may be a function of intuitively constructed mental models that depict the human body becoming much more vulnerable to harm when exposed to combinations of hazardous substances. Hence, an a priori causal theory of synergistic health benefits could be underpinned by the formation of rudimentary mental models that depict the human body becoming much more resilient to harmful substances and processes when bolstered by the presence of multiple beneficial factors.…”
Section: Discussionmentioning
confidence: 99%
“…The answer to this question was the dependent variable; choosing less than , equal to, or more than represented subadditive, additive, or synergistic judgments, respectively. This type of categorical response format has previously demonstrated validity and reliability in studies on judgments of synergistic risks (Condit & Shen, ; Dawson et al ., ).…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations